Torsion of Functionally Graded Anisotropic Linearly Elastic Circular Cylinder - ECSEDI, István; BAKSA, Attila (Engineering Transactions, 2018)
The object of this paper is Saint-Venant torsion of functionally graded anisotropic linearly elastic circular cylinder. The class of anisotropy considered has at least one plane of elastic symmetry normal to the axis of the circular cylinder. The elastic coefficients have radial dependence only. Here, we give the solution of Saint-Venant torsion problem for circular cylinder made of functionally graded anisotropic linearly elastic materials.